Outcomes Associated With Early RBC Transfusion in Pediatric Severe Sepsis: A Propensity-Adjusted Multicenter Cohort Study. Issue 1 (7th January 2022) - Muszynski, Jennifer A.; Banks, Russell; Reeder, Ron W.; Hall, Mark W.; Berg, Robert A.; Zuppa, Athena; Shanley, Thomas P.; Cornell, Timothy T.; Newth, Christopher J. L.; Pollack, Murray M.; Wessel, David; Doctor, Allan; et al.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background: Little is known about the epidemiology of and outcomes related to red blood cell (RBC) transfusion in septic children across multiple centers. We performed propensity-adjusted secondary analyses of the Biomarker Phenotyping of Pediatric Sepsis and Multiple Organ Failure (PHENOMS) study to test the hypothesis that early RBC transfusion is associated with fewer organ failure-free days in pediatric severe sepsis. Methods: Four hundred one children were enrolled in the parent study. Children were excluded from these analyses if they received extracorporeal membrane oxygenation (n = 22) or died (n = 1) before sepsis day 2. Propensity-adjusted analyses compared children who received RBC transfusion on or before sepsis day 2 (early RBC transfusion) with those who did not. Logistic regression was used to model the propensity to receive early RBC transfusion. A weighted cohort was constructed using stabilized inverse probability of treatment weights. Variables in the weighted cohort with absolute standardized differences >0.15 were added to final multivariable models. Results: Fifty percent of children received at least one RBC transfusion. The majority (68%) of first transfusions were on or before sepsis day 2. Early RBC transfusion was not independently associated with organ failure-free (−0.34 [95%CI: −2, 1.3] days) or PICU-free days (−0.63 [−2.3, 1.1]), but was associated with the secondary outcome of higher mortality (aOR 2.9 [1.1, 7.9]). Conclusions: RBC transfusion is common in pediatric severe sepsis and may be associated with adverse outcomes. Future studies are needed to clarify these associations, to understand patient-specific transfusion risks, and to develop more precise transfusion strategies.